Effect of synthetic fertilization dose on the diameter increase, height and mortality of Cinchona officinalis L. (Rubiaceae) - Fernandez Zarate, Franklin Hitler (2024)
Cinchona officinalis, is a South American tree species, commonly used for medicine, and is currently threatened by agricultural expansion and cattle ranching. The objective was to determine the effect of chemical fertilization on the nursery growth to increase growth potential and survival of C. officinalis. A completely randomized design with six treatments and three replicates was used; 20 C. officinalis plants were used per replicate. Two months after transplanting the C. officinalis seedlings to the polyethylene bags, inorganic fertilizer (YaraMila® HYDRAN) was applied. Monthly evaluations were carried out and the number of dead plants, plant height, diameter and number of leaves were recorded. The highest mortality rate was recorded when fertilizer was applied (73%) while in the non-fertilized treatment mortality reached 36%. Regarding the increase in height, diameter and number of leaves in all cases, the best results were obtained in the fertilized treatments, exceeding by 85, 70 and 17% (respectively) those obtained in the treatment to which fertilization was not applied. This study shows the effects that the application of fertilizers to C. officinalis plants at the nursery level can have on growth and mortality variables, the results suggest the use of this product for a sustainable and large-scale production of this species taking into consideration the appropriate dosage.